Enhancing the biocontrol potential of the predator Nesidiocoris tenuis through genetic selection - Pérez-Hedo, Mertixell; Ortells-Fabra, Raúl; Alonso-Valiente, Miquel; Ruiz-Rivero, Omar; Urbaneja, Alberto (Elsevier, 2023)
The zoophytophagous Nesidiocoris tenuis has proven to be a highly effective natural enemy against tomato key pests. It can enhance tomato plants' defenses due to its phytophagous behavior. However, its plant feeding can result in severe plant damage when prey is scarce. Previous studies using an isofemale line demonstrated the dietary habits of N. tenuis are genetically regulated, specifically with regard to phytophagy and zoophagy. In this study, we assessed the life-history traits of the IVIA strain, selected for over 50 generations for its zoophagy and phytophagy, compared to a commercial strain. The IVIA strain developed 3.5% faster, had 34% more offspring, preyed on 34% more Ephestia kuehniella eggs, and caused 50% fewer necrotic rings on tomato plants than the commercial strain. The IVIA strain controlled B. tabaci and T. absoluta in greenhouse experiments at the same level as the commercial strain but produced less damage to the plant. We also studied the capacity of the IVIA strain to induce plant defenses. The IVIA strain increased plant defenses compared to the control, although to a lesser extent than the commercial strain. This finding confirms the reduced phytophagy of the IVIA strain. Interestingly, the use of microsatellite markers revealed genetic differentiation between the IVIA strain and the commercial strain. Our results highlight the potential of selective breeding for improving biocontrol traits of interest in N. tenuis and open the door to differentiating selected races of N. tenuis using molecular techniques.